Injectable thermosensitive gelling delivery system for the sustained release of lidocaine. (June 2016) - Svirskis, Darren; Chandramouli, Kaushik; Bhusal, Prabhat; Wu, Zimei; Alphonso, Jolyene; Chow, Joyce; Patel, Divya; Ramakrishna, Riddhi; Yeo, Seung J; Stowers, Renus; Hill, Andrew; Munro, Jacob; et al.
Background: Patients undergoing arthroplasty require appropriate postsurgical pain relief. Analgesia is typically achieved through bolus doses of short-acting local anesthetics and with oral analgesics such as opiates, which are associated with systemic side effects. By formulating an injectable thermosensitive gelling system containing lidocaine, sustained and local delivery can be achieved following a single administration.Results: Poloxamer-based thermosensitive gelling formulations were prepared. Altering the weight ratios of poloxamers affected the sol-to-gel transition temperature, mechanical and rheological properties and in vitro drug release. Desirable formulations gelled between 28 and 33°C providing sustained release of lidocaine over 48 h.Conclusion: Thermosensitive gelling systems are promising for sustained drug release following patient administration and may be beneficial in addressing postoperative pain.